Rubens in Repeat : The Logic of the Copy in Colonial Latin America - Hyman, Aaron M., 1984- (Book collections on Project MUSE., 2021)
"This book excavates the unequaled reception of Flemish artist Peter Paul Rubens in Latin America in the form of prints made after his works, arguing that colonial artists in the New World forged new frameworks for artistic creativity by conforming to European printed designs"--